MRI-based tumor inter-fraction motion statistics for rectal cancer boost radiotherapy. (1st February 2019) - Kleijnen, Jean-Paul J. E.; van Asselen, Bram; Van den Begin, Robbe; Intven, Martijn; Burbach, Johannes P. M.; Reerink, Onne; Philippens, Marielle E. P.; de Ridder, Mark; Lagendijk, Jan J. W.; Raaymakers, Bas W.
Abstract: Background: In patients diagnosed with rectal cancer, dose escalation is currently being investigated in a large number of studies. Since there is little known on gross tumor volume (GTV) inter-fraction motion for rectal cancer, a wide variety in margins is used. Purpose of this study is to quantify GTV inter-fraction motion statistics on different timescales and to give estimates of planning target volume (PTV) margins. Material and methods: Thirty-two patients, diagnosed with rectal cancer, were included. To investigate motion from week-to-week, 16 patients underwent a pretreatment and five weekly MRIs, prior to a radiotherapy (RT) fraction of the chemoradiotherapy treatment. To investigate motion from day-to-day, the remaining 16 patients underwent five daily MRIs before each fraction in one week of RT. GTV was delineated on all scans according to guidelines. Scans were aligned on bony anatomy with the first MRI. For both datasets separately, GTV inter-fraction motion was determined based on center-of-gravity displacement. Therefrom, systematic and random errors were determined in left/right (LR), anterior/posterior and cranial/caudal (CC) direction. PTV margin estimates were calculated and evaluated on GTV coverage. Results: Systematic and random errors were found in the range of 2.3–4.8 mm and 1.5–3.3 mm from week-to-week, and 1.8–4.5 mm and 1.8–4.0 mm from day-to-day, respectively. On both timescales, similar motion patterns were found; the most motion was observed in CC whilst the least motion was observed in LR. On the week-to-week data more systematic and less random motion was observed compared to the day-to-day data. Overall, only slight differences in margin estimates were found. Derived PTV margin estimates were found to give adequate GTV coverage. Conclusion: GTV inter-fraction motion, on a week-to-week and day-to-day timescale, can be accounted for using motion statistics presented in this study.